Passivation process quality in reinforced concrete: effects of polarization periodicity and passivation consolidation parameters on data processing - Briceño-Mena, Jorge Alberto; Balancán-Zapata, Mercedes Guadalupe; Castro Borges, Pedro (Revista ALCONPAT, 2020)
The passivation process quality was studied considering polarization periodicity, passivation consolidation parameters, and data processing. Passivation process quality in steel reinforcement affects a structure’s planned future service life. Some research has addressed this phenomenon, but its study is complicated by the limits of analog-era data, dispersion in corrosion rate data, and their interpretation. Two series of small reinforced concrete specimens were built using two water/cement ratios and two curing/storage combinations and exposed to the marine environment. Polarization periodicity did not affect passivation/depassivation during passivation but on the data processing. The curing and storage process influenced the tendency towards depassivation. Post-curing storage type affected the cumulative corrosion rate from 1 to 5 µA*day/cm2; this is equivalent to the margin of uncertainty in interpretation.